RELATIONSHIP BETWEEN URIC ACID LEVELS WITH BLOOD PRESSURE OF ELDERLY IN REGION PUSKESMAS PEDAN DISTRICT KLATEN - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2018)
Background : The elderly population increases every year and cases of morbidity due to degenerative diseases are increased which includes gout and hypertension. Inflammation plays an important role in the occurrence of hypertension. Recent studies have found that uric acid is also associated with inflammatory processes. Purpose : to know how the relationship between uric acid levels with blood presseure in the elderly in work area Puskesmas Pedan Regency of Klaten. Research Methods: This research is a type of survey research (Survey Research Method). The sample used in this study is ± 60 years old elderly in the work area Puskesmas Pedan  regency of Klaten as many as 88 people with purposive sampling sampling technique. Data analysis using Chi Square test. Result : There is a significant correlation between uric acid level and blood pressure in elderly in work area Puskesmas Pedan regency of Klaten with significance value of P value = 0,000 which means P value ? 0,05 Ho is rejected. The results of this study can be concluded that the elderly who have high uric acid levels accompanied by hypertension and elderly with normal uric acid levels accompanied by normal blood pressure as well, so the hypothesis in this study accepted. Conclusion: in this study to find the relationship of uric acid levels with blood pressure, and the result is elderly who have high uric acid level also in accompanied by hypertension state.